The assessment of Global Precipitation Measurement estimates over the Indian subcontinent. Issue 8 (24th August 2017) - Murali Krishna, U. V.; Das, Subrata Kumar; Deshpande, Sachin M.; Doiphode, S. L.; Pandithurai, G.
Abstract: Accurate and real‐time precipitation estimation is a challenging task for current and future spaceborne measurements, which is essential to understand the global hydrological cycle. Recently, the Global Precipitation Measurement (GPM) satellites were launched as a next‐generation rainfall mission for observing the global precipitation characteristics. The purpose of the GPM is to enhance the spatiotemporal resolution of global precipitation. The main objective of the present study is to assess the rainfall products from the GPM, especially the Integrated Multi‐satellitE Retrievals for the GPM (IMERG) data by comparing with the ground‐based observations. The multitemporal scale evaluations of rainfall involving subdaily, diurnal, monthly, and seasonal scales were performed over the Indian subcontinent. The comparison shows that the IMERG performed better than the Tropical Rainfall Measuring Mission (TRMM)‐3B42, although both rainfall products underestimated the observed rainfall compared to the ground‐based measurements. The analyses also reveal that the TRMM‐3B42 and IMERG data sets are able to represent the large‐scale monsoon rainfall spatial features but are having region‐specific biases. The IMERG shows significant improvement in low rainfall estimates compared to the TRMM‐3B42 for selected regions. In the spatial distribution, the IMERG shows higher rain rates compared to the TRMM‐3B42, due to its enhanced spatial and temporal resolutions. Apart from this, the characteristics of raindrop size distribution (DSD) obtained from the GPM mission dual‐frequency precipitation radar is assessed over the complex mountain terrain site in the Western Ghats, India, using the DSD measured by a Joss‐Waldvogel disdrometer. Key Points: For the first time, assessment of GPM‐IMERG rainfall as well as raindrop size distribution estimates was carried over Indian subcontinent IMERG rainfall was assessed over different places in Western Ghats, India, where orography plays a major role in the monsoon precipitation Assessment was performed on daily, diurnal, monthly, and seasonal basis over Indian region